Partial slip problem for two semi-infinite strips in contact - Kartal, M; Barber, JR; Hills, D; Nowell, D (2011)
Two semi-infinite strips brought into frictional contact, end-to-end, by a normal pressure are then subjected to a monotonically increasing or oscillating tangential force remote from the interface. The full stress tensor for the partial slip regime is found. © 2010 Elsevier Ltd. All rights reserved.